The Effect of Innovation Ability and Human Resource Capability on Competitive Advantage to Improve Company Performance in Post-Pandemic Covid-19 (Empirical Study of Coffee Shop Companies in Semarang) - Novadhiyavast, Gofita Dharana Zenaislamey; Hidayati, Retno (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
This study aims to develop a conceptual model based on Innovation Capability, Human Resource Capability, and Competitive Advantage which is expected to improve coffee shop business performance. Overall, there are 200 coffee shop owners and managers involved in this research activity. The structural Equation Modelling (SEM) method was adopted as software to assist in testing models and hypotheses. Structural Equation Modelling (SEM) analyzed 200 questionnaires. The findings from this study are that good coffee shop company performance can be achieved through innovation capabilities, human resource capabilities, and competitive advantage. So, this can be used as input for related company managers to be able to get their best performance in the post-pandemic period. The results of the Goodness of fit full model SEM test still show a marginal value, namely the AGFI value (0.884) which is < the cut-off value. This study also provides several suggestions for future research development. The findings contribute to practical managerial implications by providing practitioners with some insights regarding innovation capability, human resource capability, competitive advantage, and company performance. This study explains the effect of Innovation Capability and Human Resource Capability on Company Performance both directly and through an intervening variable, namely Competitive Advantage. The conceptual model of this research was tested on coffee shop samples in Semarang.